CEO Characteristics and Board Diversity that Determine the Quality of Sustainability Reports - Damayanti, Cacik Rut; Nuzula, Nila Firdausi; Sulasmiati, Sri (Universitas Negeri Makassar, 2025)
In recent decades, sustainability has become a central concern in global business, with firms increasingly expected to disclose their social and environmental accountability through sustainability reports. These reports function not only as communication tools for stakeholders but also as indicators of transparency and corporate responsibility. The quality of sustainability reporting is closely influenced by corporate governance mechanisms, particularly CEO characteristics and board diversity. This paper aims to systematically review the literature on how these governance attributes shape sustainability disclosure based on 91 relevant articles retrieved from the Scopus database using keywords such as “CEO characteristic,” “board diversity,” and “sustainability report.” Articles were screened through inclusion and exclusion criteria, followed by bibliometric analysis using VOSviewer to identify linkages among research themes. The findings reveal a significant increase in academic attention to this topic, with Indonesia contributing substantially to the global discourse. The results indicate that CEO characteristics such as age, gender, tenure, human capital (education, international exposure), and behavioral factors. Similarly, board diversity, reflected in gender representation, professional expertise, educational background, and independence, strengthens oversight and enhances report credibility. This review concludes that CEO characteristics and board diversity are critical drivers of sustainability report quality, reinforcing corporate legitimacy and stakeholder trust. Future research is recommended to explore the dynamic interaction between CEO attributes and board composition, the cross-country variations of these effects, and the role of CEO social networks as an external governance mechanism. Such studies will deepen theoretical understanding and provide practical guidance for firms and policymakers seeking to improve sustainability accountability.